P43 Does frequent hospital review improve asthma control in children with problematic severe asthma (PSA)?. (December 2018) - Davies, BR; Frost, S; Brookes, I; Rao, S; Nagakumar, P
Abstract : Background: Children with poor asthma control despite maximally prescribed treatment have Problematic Severe Asthma (PSA). The majority of children with PSA have modifiable factors accounting for poor symptom control and are classed as having difficult asthma (DA) while a small proportion have true Severe Therapy-Resistant Asthma (STRA). Despite structured multidisciplinary (MDT) assessment and formulation of personalised management plans, a subgroup of children with PSA continue to have frequent asthma attacks. We hypothesised that frequent hospital-based review of this subgroup of children would improve asthma control and also identify those with true STRA. Methods: Eight patients under the care of the regional paediatric severe asthma service with PSA and concerns about frequent and/or life-threatening exacerbations were reviewed every 4–6 weeks in the severe asthma MDT clinic. All patients underwent prior hospital, school and home-based asthma assessment. Medication adherence was assessed by Smartinhaler device or prolonged inpatient admission. Results: Patient characteristics are described in table 1. Median duration of frequent clinical review was 8 months. Forced expiratory volume in 1 s (FEV1) improved significantly over the first six months of frequent review compared to the preceding six months – from 67% to 82% predicted (p=0.0001). This improvement was sustained after twelve months (table 2). Asthma exacerbations over a twelve month period decreased from 8.8 to 2.0 (p=0.022). Hospital admissions over twelve months also decreased from 3.4 to 0.3 but this was not statistically significant. Asthma Control Test (ACT) improved from 11.5 to 18.1 (p=0.041). Four patients were eligible for Omalizumab; one patient started Omalizumab due to ongoing poor symptom control. Asthma treatment was stepped-up for three patients and stepped-down for two patients. Discussion: A programme of frequent clinical review shows measurable benefit in a subgroup of children with PSA with multiple asthma exacerbations. In addition to reinforcing improved technique and adherence, frequent reviews enabled targeted intensive social and psychological intervention. The cost to the health service and the time cost to patients and families is likely to be offset by improvement in frequency of asthma attacks.